Targeting of vacuolar membrane localized members of the TPK channel family - Dunkel, Marcel; Schumacher, Karin (Molecular plant, 2008)
Four members of the tandem-pore potassium channel family of Arabidopsis thaliana (TPK1, 2, 3, and 5) reside in the vacuolar membrane, whereas TPK4 is a plasma membrane K+-channel. By constructing chimeras between TPK1 and TPK4, we attempted to identify channel domains involved in the trafficking process and found that the TPK1 cytoplasmic C-terminal domain (CT) is critical for the ER-as well as Golgi-sorting steps. Following site-directed mutagenesis, we identified a diacidic motif (DLE) required for ER-export of TPK1. However, this diacidic motif in the C-terminus is not conserved among other members of the TPK family, and TPK3 sorting is independent of its CT. Moreover, the 14-3-3 binding site of TPK1, essential for channel activation, is not involved in channel sorting.
Gesehen am 10.05.2017